Police Supervision of The Granting of Permits and The Use of Firearms - Hasibuan, Edi Sahputra (Jurnal Ilmiah Global Education, 2024)
Supervision and regulation on the use of firearms for members of the National Police has had special rules, especially firearms used by personnel. Supervision and use of firearms for members of the National Police into a theme that is considered serious, because it is closely related to acts of violence. Moreover, violence against oneself is reflected through the suicide of police members. This study uses normative research methods intended implementation of the use of firearms and supervision. Currently, we see that in 2024 there is news about a member of the National Police who committed suicide, namely Brigadier RAT who was found dead in an alpard car parked on Jl. Mampang Prapatan IV, South Jakarta. Based on Psychology Faculty, reza indragiri amriel explained that there is a problem of life, difficulties experienced for a long time at work can lead to suicidal thoughts. This study is limited in the scope of the police's point of view in the form of supervision and issuance of firearms permits for police personnel and is also related to the way leaders manage the workload of their personnel, organizational actions in dealing with the problem of personnel workload and protect their personnel from the risk of deviation in the use of firearms.